1996
DOI: 10.1111/j.1559-1816.1996.tb01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderation and Mediation of HIV‐Prevention Interventions: Relationship Status, Intentions, and Condom Use Among College Students1

Abstract: This study examined the effects of 2 HIV prevention interventions on condom use and mediators of condom use. College students were randomly assigned to a control condition or an intervention (communication skills or technical skills). Those who received either intervention had greater condom use self‐efficacy, more positive condom use attitudes, and stronger intentions to use condoms than did controls. Furthermore, 3‐month follow‐up data revealed that students in either intervention who were not in a steady da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 54 publications
2
53
0
1
Order By: Relevance
“…This strategy is easy to explain and apply, and these features qualify self-efficacy interventions based on forming ''if -then'' plans (i.e., implementation intentions) as very cost efficient. But will interventions based on implementation intentions produce stable effects over time as is observed with other intervention programs (e.g., Sanderson, & Jemmott, 1996)? Possibly, individuals who use self-efficacy strengthening implementation intentions quickly recognize that this strategy allows for a higher test performance, and thus will again use such selfinstructions in other test situations.…”
Section: Self-efficacy Interventionsmentioning
confidence: 96%
See 1 more Smart Citation
“…This strategy is easy to explain and apply, and these features qualify self-efficacy interventions based on forming ''if -then'' plans (i.e., implementation intentions) as very cost efficient. But will interventions based on implementation intentions produce stable effects over time as is observed with other intervention programs (e.g., Sanderson, & Jemmott, 1996)? Possibly, individuals who use self-efficacy strengthening implementation intentions quickly recognize that this strategy allows for a higher test performance, and thus will again use such selfinstructions in other test situations.…”
Section: Self-efficacy Interventionsmentioning
confidence: 96%
“…The benefits of intervention programs to install high self-efficacy beliefs have been amply demonstrated. For example, in a study by Sanderson and Jemmott (1996), participants who received a behavioral intervention program focusing on communication skills or technical skills to facilitate HIV prevention showed greater condom use self-efficacy, more positive condom use attitudes, and stronger intentions to use condoms than did controls. Three-month follow-up data revealed that participants who were not in a steady dating relationship but had received this intervention reported more consistent condom use than did control participants.…”
Section: Self-efficacy Interventionsmentioning
confidence: 99%
“…Recently, Rotheram-Borus, Reid, Rosario, and Kasen (1995) have shown that efficacious gay persons were more likely to abstain from risky sexual practices or to use condoms than less efficacious persons. Similarly, Sanderson and Jemmott ( 1996) demonstrated that adolescents who participated in an intervention intended to boost their efficacy were more likely to use condoms than were members of a control group who had not experienced this intervention. Thus, it appears that in this area, the moderator effect of efficacy on the relation between attitudes and behavior has been established, suggesting its usefulness in the prediction of the transition toward nonvirginity as well.…”
mentioning
confidence: 98%
“…the reviews by Fisher &Fisher, 1992, andSanderson &Jemmott, 1996). Recently, Rotheram-Borus, Reid, Rosario, and Kasen (1995) have shown that efficacious gay persons were more likely to abstain from risky sexual practices or to use condoms than less efficacious persons.…”
mentioning
confidence: 99%
“…It measures an individual's intentions to use condoms in the future. It was modeled after the Intentions to Use Condoms scale developed by Sanderson and Jemmott (1996). A typical item is: "How likely is it that you will use condoms if you decide to have sex in the next 6 months?"…”
Section: (8) Behavioralmentioning
confidence: 99%